IBM SPSS Modeler Essentials : Effective techniques for building powerful data mining and predictive analytics solutions /: Effective techniques for building powerful data mining and predictive analytics solutions. (2017) - McCormick, Keith; Salcedo, Jose Jesus
No abstract available